Identification of Characteristics of E-Cigarettes (Vape) in Jayapura City - Wahyuti, Wahyuti; Mamoribo, Sherly N.; Violita, Fajrin (Universitas Mandala Waluya, 2025)
The problem of e-cigarette (vape) use in Indonesia is increasingly worrying, especially among adolescents and young people. The assumption that vaping is safer than conventional cigarettes has contributed to the increase in young users. This study aims to describe the characteristics of vape users in Jayapura City with a quantitative descriptive design and cross-sectional approach. The study was conducted in 4 sub-districts with a total sample of 300 people, selected by accidental sampling of vape users in various cafes. Data were collected through interviews using a questionnaire and analyzed univariately with SPSS. The results showed that the majority of users were aged 15-24 years (51.4%), male (69.3%), highly educated (52.7%), Protestant (59.3%), Non-Papuan (76.0%), unmarried (85.3%), and lived with parents (52.3%). The most common duration of use was 3-4 years (48.3%), the most commonly used device was Box Mod (36.3%), and most used less than three types of liquid (65.7%). These results suggest the need for education specifically targeted at young and highly educated groups regarding the long-term health risks of e-cigarette use.